PENGARUH UKURAN PERUSAHAAN (SIZE), PROFITABILITAS DAN KEPEMILIKAN INSTITUSIONAL TERHADAP CORPORATE SOCIAL RESPONSIBILITY (CSR) (Students' Journal of Accounting and Banking, 2015)
The study aimed to examines the effect of size, profitability, and institutional ownership on Corporate Social Responsibility (CSR). The data used is annual report of companies listed in Indonesia Stock Exchange 2012-2013 period. The sampling method used purposive sampling. The results showed that size and profitability has significant effect on Corporate Social Responsibility (CSR). Whereas the institutional ownership had no significant effect on Corporate Social Responsibility (CSR).Keywords: Size, Profitability, Institutional Ownership, and CSR